Wear resistance of structural steels nitroded in cyclic-commuted discharge at limit modes of friction - Stechyshyn, M.S.; Lyukhovets, V.V.; Stechyshyn, N.M.; Tsepenyuk, M.I. (Problems of Tribology, 2022)
The article discusses the method of conducting tribological studies at the limit modes of friction of nitrided and non-nitrided steels 20 and 45 in order to achieve a comparison of the results of laboratory tests with operational data. The relationship of structural phases in time is significantly influenced by the initial state of the surface and its physical and mechanical characteristics, pressure on the contact surface, sliding speed, and all these parameters for the limit mode of friction are closely related. Carrying out tests on the wear resistance of samples made of different materials and with significantly different characteristics of the surface layer at the same parameters of the test regime is impossible in most cases, since the obtained results are problematic to compare.